Microgrid Islanding Detection with Voltage Phase Angle Method - Raju Lingampalli, Bangar; Rao Kotamraju, Subba; Kumar M, Kiran; Reddy, C. Rami (Journal of Electronic Design Engineering, 2023)
Distributed Generation (DG) into Microgrid has become a challenge to the researchers for the control and stability. The Microgrid must detect islanding when there is an unintentional fault on the system and bring Microgrid to islanding mode seamlessly in less than 2 seconds, as per IEEE-1547-2018 standards. It is also the basic requirement as per standards to be stable and avoid nuisance tripping to feed the loads without interruption during non-islanding events like load connection and disconnection. There are many islanding detection methods like passive, active and communication but the passive methods leave behind a large Non-Detection Zone (NDZ) at a lower percentage mismatch power. The islanding detection time is more at a lower percentage mismatch power. Keeping in view all these facts, a simple passive islanding detection method, Rate of Change of Voltage Phase Angle (ROCOVPA) is proposed. In this method, the voltage phase angle at the targeted DG is measured first and then differentiated to detect the islanding condition. The method is tested against unsymmetrical faults as these are common. This method is also compared with the widely used method, Rate of Change of Frequency (ROCOF) in MATLAB / Simulink environment and found to be effective without power quality problems, as there are no injections during testing.